A contourite depositional system along the Uruguayan continental margin: sedimentary, oceanographic and paleoceanographic implications - Hernandez Molina, F.Javier; Soto, Matias; Piola, Alberto Ricardo; Tomasini, Juan; Preu, Benedict; Thompson, Phil; Baldini, Gianluca; Creaser, Adam; Violante, Roberto Antonio; Morales, Ethel; Paterlini, Marcelo; De Santa Ana, Hector (Marine Geology)
For the first time, a multidisciplinary approach to evaluate the influence of bottom currents in the Uruguayan continental margin is presented. Bathymetric data and multichannel 2D and 3D seismic reflection profiles were used to construct a morphosedimentary map to interpret and decode sedimentary and oceanographic processes along the Uruguayan continental margin. Based on these results, an extensive contourite depositional system on the margin is described, which contains an impressive array of large erosive, depositional (drifts) and mixed (terrace) features, which have been generated primarily by the near-bottom flows associated with water masses of Antarctic and subantarctic origin. From the Eocene–Oligocene boundary up to present time, the long-term influence of water masses from higher southern latitudes, in combination with down-slope sedimentary processes have strongly controlled the overall margin morphology. Most of the features described here, were formed during the middle/late Miocene epoch due to paleoceanographic shifts that include the arrival of Antarctic Intermediate Water along the margin, which in combination with deeper Antarctic Bottom Water are fundamental in the margin evolution. In combination with Quaternary climatic and eustatic changes in sea level, fluctuations of the Brazil–Malvinas Confluence influenced subsequently glacial and interglacial stages as recognized in sedimentary features defined here. These paleoceanographic changes controlled the sedimentary stacking pattern and the locations of high amplitude reflections along the contourite terraces, which could be associated with sandy deposits. A more detailed understanding of the margin will improve interpretations of variations in the South Atlantic subtropical gyre and further constrain general climatic and ocean circulation models. Fil: Hernandez Molina, F.Javier. University of London; Reino Unido Fil: Soto, Matias. ANCAP; Uruguay Fil: Piola, Alberto Ricardo. Consejo Nacional de Investigaciones Científicas y Técnicas; ...